THE ROLE OF GERMANY IN EUROPEAN SECURITY AFTER REUNIFICATION - Mossa Hussen (European Scientific Journal, ESJ, 2012)
The end of the Second World War brought a new kind of system and of stability in Europe that they never had experienced before. The war, occupation, and postwar European institutions transformed Germany profoundly both internally and externally by linking its foreign and security policy to multilateral frameworks. The new Germany is not a major military power like the old German empire, rather the most powerful civilian, economic and political actor that have the capability to influence policies in Europe and beyond without employing military power.